Squirrel's World - Moser, Lisa.; Gorbachev, Valeri (Cambridge, MA : Candlewick Press, 2007)
Squirrel's well-meaning attempts to help his forest friends do not always turn out as planned.
Keywords: Squirrels -- Fiction; Forest animals -- Fiction; Helping behavior -- Fiction; Animals -- Fiction; Fiction